Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1155/s1064744901000333
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Escherichia coli Isolated From FemaleReproductive Tract Infections and Neonatal Sepsis

Abstract: Objective: The presence of enterobacteria such as Escherichia coli in the vagina of normal women is not synonymous with infection. However, vaginal E. coli may also cause symptomatic infections. We examined bacterial virulenceproperties that may promote symptomatic female reproductive tract infections (RTI) and neonatal sepsis. Methods: E. coli isolated as the causative agent from cases of vaginitis (n = 50), tubo-ovarian abscess (n = 45) and neonatal sepsis (n = 45) was examined for selected phenotypic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
(26 reference statements)
4
18
0
Order By: Relevance
“…The presence of other bacteria such as E. coli may be important, although not necessarily synonymous with infection (Cook et al, 2001). The ability of some E. coli strains to adapt to the vaginal and/or endocervical conditions and to the amniotic fluid, as well as the ability to invade the blood or the cerebrospinal fluid of neonates, correlates with an enrichment of VFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of other bacteria such as E. coli may be important, although not necessarily synonymous with infection (Cook et al, 2001). The ability of some E. coli strains to adapt to the vaginal and/or endocervical conditions and to the amniotic fluid, as well as the ability to invade the blood or the cerebrospinal fluid of neonates, correlates with an enrichment of VFs.…”
Section: Discussionmentioning
confidence: 99%
“…A cluster of sfa and foc genes is necessary for the biogenesis of S and F1C fimbriae (Khan et al, 2000). Johnson et al (2002) reported a frequency of 61 % sfa/foc-positive isolates from infants with NBM, whilst other studies have shown that this percentage is lower (33-44 %; Bingen et al, 1997;Watt et al, 2003), whereas the percentage of E. coli strains with sfa or sfa/foc genes isolated from blood ranges from 9 to 59 % (Bingen et al, 1997;Cook et al, 2001;Watt et al, 2003;Bagger-Skjøt et al, 2007;Soto et al, 2008). In addition, E. coli strains isolated from the vagina frequently possess genes encoding S fimbriae or S and F1C pili (20-48 %; Obata-Yasuoka et al, 2002;Watt et al, 2003;Hilbert et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A complex and intricate balance of microorganisms maintains the normal vaginal flora and changes with a multitude of events in the patient"s life (Cook, et al, 2001). The dominant microbial species is Lactobacillus, which maintains the generally acidic vaginal pH (Khan and Khan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence in the vagina of other bacteria such as Gardnerella vaginalis, group B streptococci and Esherichia coli termed commensal bacteria (Laren and Monif, 2001) is not synonymous with infection (Cook, et al, 2001). According to Hammill (1989), the incidence of E. coli in the vagina of normal, pre-menopausal, nonpregnant, asymptomatic women is about 21%.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, aerobic vaginitis may be a better candidate than bacterial vaginosis as the cause of pregnancy complications, such as ascending chorioamnionitis, preterm rupture of the membranes and preterm delivery [4]. An extensive analyses of phylogenetic group and virulence factors of E. coli isolated from females reproductive tract infection (RTI) were carried out [7][8][9][10]. In these studies, it was found that vaginal E. coli have unique properties that may enhance their virulence.…”
Section: Introductionmentioning
confidence: 99%